Dynamic volumetric changes of hippocampal subfields in clinically isolated syndrome patients: A 2-year MRI study. (August 2019) - Cacciaguerra, Laura; Pagani, Elisabetta; Mesaros, Sharlota; Dackovic, Jelena; Dujmovic-Basuroski, Irena; Drulovic, Jelena; Valsasina, Paola; Filippi, Massimo; Rocca, Maria Assunta
Background: Different subregional patterns of hippocampal involvement have been observed in diverse multiple sclerosis (MS) phenotypes. Objective: To evaluate the occurrence of regional hippocampal variations in clinically isolated syndrome (CIS) patients, their relationships with focal white matter (WM) lesions, and their prognostic implications. Methods: Brain dual-echo and three-dimensional (3D) T1-weighted scans were acquired from 14 healthy controls and 36 CIS patients within 2 months from clinical onset and after 3, 12, and 24 months. Radial distance distribution was assessed using 3D parametric surface mesh models. A cognitive screening was also performed. Results: Patients showed clusters of reduced radial distance in the Cornu Ammonis 1 from month 3, progressively extending to the subiculum, negatively correlated with ipsilateral T2 and T1 lesion volume. Increased radial distance appeared in the right dentate gyrus after 3 ( p < 0.05), 12, and 24 ( p < 0.001) months, and in the left one after 3 and 24 months ( p < 0.001), positively correlated with lesional measures. Hippocampal volume variations were more pronounced in patients converting to MS after 24 months and did not correlate with cognitive performance. Conclusion: Regional hippocampal changes occur in CIS, are more pronounced in patients converting to MS, and are modulated by focal WM lesions.